Response of consumer and research grade indoor air quality monitors to residential sources of fine particles. (14th May 2018) - Singer, B. C.; Delp, W. W.
Abstract: The ability to inexpensively monitor PM2.5 to identify sources and enable controls would advance residential indoor air quality (IAQ) management. Consumer IAQ monitors incorporating low‐cost optical particle sensors and connections with smart home platforms could provide this service if they reliably detect PM2.5 in homes. In this study, particles from typical residential sources were generated in a 120 m 3 laboratory and time‐concentration profiles were measured with 7 consumer monitors (2‐3 units each), 2 research monitors (Thermo pDR‐1500, MetOne BT‐645), a Grimm Mini Wide‐Range Aerosol Spectrometer (GRM), and a Tapered Element Oscillating Microbalance with Filter Dynamic Measurement System (FDMS), a Federal Equivalent Method for PM2.5 . Sources included recreational combustion (candles, cigarettes, incense), cooking activities, an unfiltered ultrasonic humidifier, and dust. FDMS measurements, filter samples, and known densities were used to adjust the GRM to obtain time‐resolved mass concentrations. Data from the research monitors and 4 of the consumer monitors—AirBeam, AirVisual, Foobot, Purple Air—were time correlated and within a factor of 2 of the estimated mass concentrations for most sources. All 7 of the consumer and both research monitors substantially under‐reported or missed events for which the emitted mass was comprised of particles smaller than 0.3 μm diameter.